Pengaruh Jenis Otot dan Lama Penyimpanan terhadap Kualitas Daging Sapi - Rahim, Syafrida (Fakultas Peternakan Universitas Jambi, 2009)
This research was conducted at the Laboratory of Livestock Production Faculty of Animal Husbandry, Jambi University in 2008. The research aimed to find out the muscle type and the effect of storage of beef quality. Research was arranged in Randomized Block Design with three replications comprising a factorial combination of two muscle type (Longissimus Dorsi/LD, Bicepps Femoris/BF), and four level of storage duration (P3/3 days, P6/6 day,P9/9 days and P12/12 days). Data of lost weight,the number of droplets (drip,) meat pH and mature lost was taken. The results showed that there was no interaction between the type of muscle with a long storage. Muscle type did not significantly affected (P> 0.05) lost weight, drip, and pH. Storage duration had significant effect (P <0.01) to lost weight and drip, but had no effect (P> 0.05) to mature weight on meat pH. Based on Duncan's test, the lost weight of the P12> Q9> P3> P6. For the amount of drip in treatment P12> Q9 = P3> P6. The conclusion of this study that the type of muscle did not affect the quality of meat, but longer storage affected thequality of the meat on the weight decrease in the number of droplets (drip). Storage meat for 6 days (P6)had a good meat quality.